2000
DOI: 10.1152/ajpheart.2000.279.3.h976
|View full text |Cite
|
Sign up to set email alerts
|

Early sequence of cardiac adaptations and growth factor formation in pressure- and volume-overload hypertrophy

Abstract: To investigate the time sequence of cardiac growth factor formation, echocardiographic and hemodynamic measurements were performed at scheduled times, and mRNAs for angiotensinogen, prepro-endothelin-1 (ppET-1), and insulin-like growth factor I (IGF-I) were quantified with RT-PCR and localized with in situ hybridization in pigs (fluothane anesthesia) by use of pressure or volume overload (aortic banding and aorta-cava fistula, respectively). Relative peptide formation was also measured by radioimmunoassay. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
58
1
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(64 citation statements)
references
References 45 publications
2
58
1
2
Order By: Relevance
“…Transgenic mice with cardiac restricted overexpression of TNF-a present progressive LV dilation (Sivasubramanian et al, 2001), and the activation of IL-6 receptor transmembranar domain gp130 in isolated neonatal rat cardiomyocytes induces sarcomere longitudinal growth (Wollert et al, 1996). RV IGF-1 overexpression in P-Band was similar to Dextran, in accordance with previous studies showing an upregulation of this gene in pressure and volume overload (Modesti et al, 2000(Modesti et al, , 2004. Given its pro-hypertrophic and anti-apoptotic actions, IGF-1 might contribute to myocardial adaptation to cardiac overload (Tanaka et al, 1998;Welch et al, 2002).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Transgenic mice with cardiac restricted overexpression of TNF-a present progressive LV dilation (Sivasubramanian et al, 2001), and the activation of IL-6 receptor transmembranar domain gp130 in isolated neonatal rat cardiomyocytes induces sarcomere longitudinal growth (Wollert et al, 1996). RV IGF-1 overexpression in P-Band was similar to Dextran, in accordance with previous studies showing an upregulation of this gene in pressure and volume overload (Modesti et al, 2000(Modesti et al, , 2004. Given its pro-hypertrophic and anti-apoptotic actions, IGF-1 might contribute to myocardial adaptation to cardiac overload (Tanaka et al, 1998;Welch et al, 2002).…”
Section: Discussionsupporting
confidence: 90%
“…In the intact heart, acute pressure and volume overload induced different local growth factor formation (Modesti et al, 2000). This was associated with distinct hemodynamics and specific patterns of ventricular remodeling (concentric vs. eccentric hypertrophy) (Modesti et al, 2000(Modesti et al, , 2004.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In-vivo studies in pig heart showed that the early release of Ang II stored in the cardiomyocyte cytoplasm granules [3] was followed by an increase in the mRNA of preproET-1 and angiotensinogen with final ET-1 release and recovery of cardiac contractility [2]. ET-1 gene expression and peptide release, as well as the recovery of contractility, were all abrogated by AT1 receptor blockade [3].…”
Section: Discussionmentioning
confidence: 99%
“…Early growth factor formation following the application of mechanical stimuli is also mediated by Ang II as suggested by the observation that the inhibition of type I receptors for Ang II inhibited early growth factor (ET-1 and angiotensinogen) overexpression in stretched myocytes in vitro [1] and in experimental models of acute cardiac overload in vivo [2,3]. However, in patients with aortic valve disease, the progression from compensatory hypertrophy to heart failure is characterized by reduced gene expression of ventricular myocytes and cardiac formation of insulin-like growth factor-1 (IGF-I) and ET-1 [4], notwithstanding a significant increase in cardiac Ang II generation [4].…”
Section: Introductionmentioning
confidence: 99%